BioRegistry: Automatic extraction of metadata for biological database retrieval and discovery. (7th July 2010) - Devignes, Marie-Dominique; Franiatte, Philippe; Messai, Nizar; Bresso, Emmanuel; Napoli, Amedeo; Smail-Tabbone, Malika
The need for a well-maintained searchable directory is an important issue with regard to the numerous biological databases produced by genomic and post-genomic research. The BioRegistry repository aims to associate content metadata belonging to a biomedical thesaurus with biological databases in view of retrieval or discovery. It is automatically generated from a publicly available list of biological databases. The querying modalities include a search by semantic similarity. The system performance is evaluated in terms of precision and recall on a collection test. A classification method is proposed for browsing and discovering databases through the BioRegistry.